2009
DOI: 10.1016/j.jacc.2008.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Eisenmenger Syndrome

Abstract: Eisenmenger syndrome (ES), the most advanced form of pulmonary arterial hypertension (PAH) associated with congenital heart disease, is a devastating condition that has a considerable impact on patients' lives. Patients who develop ES typically exhibit 1 or more of a range of cardiac defects, including ventricular septal defects, atrial septal defects, and patent ductus arteriosus. The nature of the congenital defect underlying ES is important because it has prognostic implications. Although ES shares similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(45 citation statements)
references
References 58 publications
1
39
0
5
Order By: Relevance
“…4,5 The underlying pathology in EIS patients is typically a large, unrestrictive ventricular septal defect that exposes the pulmonary vasculature to excessive blood flow and pressures, eventually leading to irreversible pulmonary hypertension. 6,7 Although no pediatric data are available for comparison, our overall survival of EIS patients undergoing lung transplantation is similar to that for adults, with our longest survivor being 13 years post-transplant. 8,9 While encouraging, our results should be contrasted with the natural history studies on Eisenmenger syndrome that have shown a 3-year survival from time of diagnosis of 77% and a 25-year survival from time of diagnosis of 42%.…”
Section: Discussionmentioning
confidence: 87%
“…4,5 The underlying pathology in EIS patients is typically a large, unrestrictive ventricular septal defect that exposes the pulmonary vasculature to excessive blood flow and pressures, eventually leading to irreversible pulmonary hypertension. 6,7 Although no pediatric data are available for comparison, our overall survival of EIS patients undergoing lung transplantation is similar to that for adults, with our longest survivor being 13 years post-transplant. 8,9 While encouraging, our results should be contrasted with the natural history studies on Eisenmenger syndrome that have shown a 3-year survival from time of diagnosis of 77% and a 25-year survival from time of diagnosis of 42%.…”
Section: Discussionmentioning
confidence: 87%
“…The treatment regime to be adopted for pulmonary hypertension in Eisenmenger syndrome is mainly based on clinical experts consensus [4]. Long term oxygen therapy is able to reduce dyspnoea and, although there is a lack of literature support, specific drugs such as endothelin receptor antagonists, phosphodiesterase type-5 inhibitors and prostacyclin analogues, may be indicated for pulmonary hypertension [5,6,7,8]. Management of concomitant bleeding and clotting increased risk is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 50% of all patients with large unrepaired VSD, and approximately 10% of patients with large unrepaired ASD, are at risk for Eisenmenger's syndrome. A left-to-right shunt lesion increases the pulmonary blood flow, changing the vascular structure and leading to a rise in PAP [11]. Nevertheless, despite having established long-standing pulmonary vascular disease with evidence of significant vascular remodeling/obstruction, Eisenmenger patients often respond favorably to advanced therapy [12].…”
Section: Discussionmentioning
confidence: 99%